Four-Laning of Highways Through Public Private Partnership Manual of Specifications and Standards - Planning Commission (Planning Commission, 2006)
The Eleventh Plan envisages an investment of Rs. 3,14,152 crore (US$ 80 billion) in the road sector, of which Rs. 1,06,792 crore (US$ 27 billion) is expected from Public Private Partnerships (PPPs) that would serve as the vehicle for attracting private capital in public infrastructure projects aimed at improving efficiencies and reducing costs. Besides the Central Government, several states are pursuing PPPs for developing their respective highways. A well-defined policy and regulatory framework consistent with international best practices has since been adopted for application to PPP projects in the highway sector. This is reflected in the standardised documents for bidding and award of projects. In particular, the Government of India has adopted a Model Concession Agreement (MCA) for PPPs in National Highways. on similar lines, the Planning Commission has published an MCA for State Highways. These MCAs follow the Design, Build, Finance and Operate (DBFO) approach that requires the Concessionaire to bear the responsibility for detailed design. However, the responsibility for providing safe and reliable roads ultimately rests with the Government and the MCA, therefore, mandates a Manual of Standards and Specifications that the concessionaire must conform to.
Planning Commission Government of India
Planning Commission Government of India